Initial stages in functionalization of polystyrene upon treatment with oxygen plasma late flowing afterglow. (19th September 2018) - Vesel, Alenka; Zaplotnik, Rok; Kovac, Janez; Mozetic, Miran
Abstract: A remote microwave discharge was applied as a source of oxygen (O) atoms for treatment of polystyrene in the preparation chamber of an x-ray photoelectron spectroscopy (XPS) instrument. The density of O atoms as measured with a calibrated catalytic probe was 2 × 10 18 m −3 . Such a small O atom density allowed for investigating the initial stages of polymer functionalization. The samples were subjected to various fluences of O atoms from approximately 2 × 10 21 to 3 × 10 23 m −2, and the functional groups were determined by XPS without breaking vacuum conditions. The results showed rapid destruction of the aromatic rings even at low O atom fluences. The initial functionalization caused the formation of hydroxyl groups followed by carbonyl groups, but the measurable amount of the carboxyl or ester groups, let alone carbonate, appeared only after the fluence of approximately 1 × 10 22 m −2 . The concentration of functional groups of the high XPS binding energy shift increased at elevated fluences until it became comparable with those of the low energy shift at the largest fluence used in this investigation, i.e. 3 × 10 23 m −2 . The O concentration on the polymer surface as determined from XPS survey spectra was first rapidly increasing up to the fluence of a few 10 22 m −2 and then continue increasing slowly with the increasing fluence even beyond 1 × 10 23 m −2 . This investigation, which was performed in situ, gives us new knowledge for understanding the initial steps of polymer functionalization.